Anthrax in the Territory of Dagestan - A. N. Kulichenko; N. P. Buravtseva; S. N. Antyuganov; E. Ya. Omarieva; A. G. Ryazanova; E. I. Eremenko; V. M. Mezentsev; O. I. Tsygankova; G. D. Bryukhanova; A. A. Gadzhieva; I. G. Alzhanbekova; D. M. Bammatov (Проблемы особо опасных инфекций, 2013)
The aim of the study is to investigate anthrax epizootiologic and epidemiologic situation in the Republic of Dagestan over the period of 1944–2010. Anthrax morbidity has been registered in 38 regions and Makhachkala. All in all 1001 anthrax cases and 3128 sick rural animals have been registered. Determined are 420 anthrax specified potentially hazardous areas (SPHA), the majority of them (77.4 %) have formed before 1969. Regions of the republic have been checked against the level of risk connected with anthrax infecting over the last 40 years. Therewith, they have been classified into three groups: with low, medium, and high epizootiological-and-epidemiological potential. 15 regions with high epizootiological-and-epidemiological potential have been marked as potentially hazardous on a regular basis. These regions occupy 31 % of the republic`s territory and 52.5 % of the SPHA territory. 84 % of patients and 88 % of fallen animals have been registered there for the past 40 years.